Pelatihan Pembuatan Media Pembelajaran Poster Digital Berbasis Barcode - Risma Anita Puriani; Romi Fajar Tanjung; Ratna Sari Dewi; Abi Burhan (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
The independent curriculum demands learning activities and guidance and counseling services in terms of technology-based student development, where the educational information delivered is packaged attractively and is easily accessible anywhere. This training aims to improve educators' skills in creating educational materials in the form of barcode-based digital posters. The number of respondents in this service activity was 42 people. Data collection used a training instrument for making barcode-based digital poster learning media. Data analysis using the Google Form application. The results of the training found that training in making barcode-based digital poster learning media was very useful for the participants. Research data found that there was an increase in skills in using the Canva application and the S.ID application. Implications in guidance and counseling services can provide interactive guidance and counseling services, especially in providing basic services as well as individual specialization and planning.